An Evolutionary Perspective of Nutrition and Inflammation as Mechanisms of Cardiovascular Disease - Rubio-Ruiz, María Esther (Int J Evol Biol, 2015)
When cardiovascular diseases are viewed from an evolutionary biology perspective, a heightened thrifty and an inflammatory design could be their mechanisms. Human ancestors confronted a greater infectious load and were subjected to the selection for proinflammatory genes and a strong inflammatory function. Ancestors also faced starvation periods that pressed for a thrifty genotype which caused fat accumulation. The pressure of sustaining gluconeogenesis during periods of poor nourishment selected individuals with insulin resistance. Obesity induces a proinflammatory state due to the secretion of adipokines which underlie cardiometabolic diseases. Our actual lifestyle needs no more of such proinflammatory and thrifty genotypes and these ancestral genes might increase predisposition to diseases. Risk factors for atherosclerosis and diabetes are based on inflammatory and genetic foundations that can be accounted for by excess fat. Longevity has also increased in recent times and is related to a proinflammatory response with cardiovascular consequences. If human ancestral lifestyle could be recovered by increasing exercise and adapting a calorie restriction diet, obesity would decrease and the effects on chronic low-grade inflammation would be limited. Thereby, the rates of both atherosclerosis and diabetes could be reduced.